2014
DOI: 10.1038/leu.2014.281
|View full text |Cite
|
Sign up to set email alerts
|

Hes1 suppresses acute myeloid leukemia development through FLT3 repression

Abstract: In leukemogenesis, Notch signaling can be up and downregulated in a context-dependent manner. The transcription factor hairy and enhancer of split-1 (Hes1) is well-characterized as a downstream target of Notch signaling. Hes1 encodes a basic helix-loop-helix-type protein, and represses target gene expression. Here, we report that deletion of the Hes1 gene in mice promotes acute myeloid leukemia (AML) development induced by the MLL-AF9 fusion protein. We then found that Hes1 directly bound to the promoter regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 48 publications
2
28
0
Order By: Relevance
“…Curiously, the expression of several Notch-related genes, including Hes1, a known downstream target of Notch signaling, was increased after TKI exposure in both FLT3/ITD + AML primary samples and cell lines. Notably, Takayasu Kato et al 31 reported that Hes1 binds directly to the promoter region of the FLT3 gene and downregulates promoter activity. It has also been reported that the Hes1 protein directly binds to STAT3 and promotes STAT3 phosphorylation and activation.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, the expression of several Notch-related genes, including Hes1, a known downstream target of Notch signaling, was increased after TKI exposure in both FLT3/ITD + AML primary samples and cell lines. Notably, Takayasu Kato et al 31 reported that Hes1 binds directly to the promoter region of the FLT3 gene and downregulates promoter activity. It has also been reported that the Hes1 protein directly binds to STAT3 and promotes STAT3 phosphorylation and activation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies described the poor activation of Notch in AML samples [11, 12, 28]. Nevertheless, accumulating evidence highlighted the role of Notch in the interaction between bone marrow microenvironment and leukemia cells by showing that hBM-MSCs are capable of inducing activation of Notch signalling in different cancer cells, including multiple myeloma, CLL, and T-ALL [4, 5, 29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HES1 was involved in cell cycle, and maintained multipotent precursor cells in an undifferentiated state in several tissues during development and adulthood [22]. Recently, it was reported that HES1 acted as a tumor suppressor in MLL-AF9 AML mice model [10].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies found that overexpression of HES1 inhibited cycling of hematopoietic stem and progenitor cells (HSPCs) in vitro and cell expansion in vivo, associated with upregulation of p21 [9]. Recently, it was reported that HES1 acted as a tumor suppressor in MLL-AF9 AML mice model [10]. But the role of HES1 in primary AML cells with other gene mutations and AML cell lines has not been well demonstrated.…”
Section: Introductionmentioning
confidence: 98%